06 Possible role of the ultra-rapid delayed rectifier potassium current (IKur) in action potential repolarisation in rabbit heart. Issue 1 (10th December 2010) - Cui, Y; Wilson, C; Turner, S; Graham, S; McMahon, N; Heath, B
Abstract : The ultra-rapid delayed rectifier K+ current (IKur) plays an important role in early cardiac action potential repolarisation in a number of species. Although the rabbit heart has proven useful for studying cardiac repolarisation, the role of IKur in rabbit heart is less well known, as is the potential contribution of this ion channel to drug-induced changes in repolarisation. The aim of this study was to investigate the effects of 4-aminopyridine (4-AP) and 2-isopropyl-5-methylcyclohexyl diphenylphosphine oxide (DPO-1) on action potential duration (APD) in isolated rabbit atria and ventricular papillary muscles. Intracellular action potentials were recorded at 36–37°C and APD was measured at 20, 50 and 90% repolarisation (APD20, 50 and 90). Exposure to 4-AP at 50 μM for 30 min caused a significant prolongation in APD20 of 29.0±3.3% and 39.4±9.4% in left atria and right ventricular papillary muscles, respectively (stimulated at 1 Hz). In contrast, late repolarisation was less affected; increases in APD90 were 8.6±2.8% and 18.7±5.0% for atria and papillary muscles, respectively. The prolongation was reverse frequency dependent (0.2–1 Hz). Similarly, application of DPO-1 at 0.3 μM for 30 min significantly prolonged APD20 by 21.9±8.8% and 45.8±23.0% in atria and papillary muscles, respectively. APD90 was less affected, with increases of 10.8±2.2 and 25.2±13.2% in atria and papillary muscles, respectively. In conclusion, it is likely that IKur may play a functional role in repolarisation in rabbit in both atria and ventricle.